What Is the Role of Pharmacists in Treating COVID-19 Patients? The Experiences and Expectations of Front Line Medical Staff - Jia, Xuedong; Zhang, Wan; Du, Shuzhang; Wen, Linlin; Li, Hongye; Yin, Zhao; Li, Jun; Zhang, Xiaojian (Frontiers in Public Health, 2021)
Aims: To understand the role of pharmacists in the treatment of COVID-19 patients from the perspective of front line medical staff, understand the core values of pharmacists and the professional expectations of medical staff for pharmacists, and provide reference information for the career growth path of future pharmacists. Methods: A phenomenological method was used to conduct in-depth interviews with front line medical staff working in isolation wards during COVID-19, and the interview data were analyzed in depth and the topics were extracted. Results: Pharmacists played a positive role in ensuring the supply of special drugs, including hospital protective preparations, drug information, medication consultation for complex patients, and identification of adverse drug reactions and interactions in the process of air defense of the epidemic. However, at present, the integration of pharmacists and nursing team is poor, the communication is less, and the pharmaceutical care coverage of the physician team is still not comprehensive. Conclusions: The level of pharmaceutical care of pharmacists needs to be further strengthened. Front-line clinical medical teams generally have high professional expectations for pharmacists, expecting pharmacists in the future to become drug therapy experts, who will fully participate in clinical work and clinical issue decision-making, and especially play a central role in the judgment of drug interactions, drug contraindications identification and other aspects.